(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article highlights the role and importance of modern diagnostic methods in identifying infectious diseases. In today’s globalization, the rapid spread of infectious diseases, the emergence of their new forms, and mutations are further intensifying the need for an effective diagnostic system. Modern laboratory tests, molecular-genetic examinations, express tests, and digital medicine technologies play a crucial role in the early detection of diseases, assessment of risk levels, and prevention of epidemics. The article analyzes the advantages of these technologies, their application in practice, and their impact on the healthcare system. Furthermore, proposals and recommendations are provided for improving the diagnostic process, controlling infections, and enhancing medical safety. The research results indicate that modern diagnostic methods are a decisive factor not only in saving patients’ lives but also in protecting public health in general.